2015
DOI: 10.1007/s00253-015-7143-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a novel variant of human tumor necrosis factor-related apoptosis-inducing ligand from the rhesus monkey, Macaca mulatta

Abstract: Human tumor necrosis factor-related apoptosis-inducing ligand (hTRAIL) and its variants are attractive antitumor drug candidates. The predicted amino acid sequence of the functional extracellular domain of Macaca mulatta TRAIL (mmTRAIL) was found to differ from that of hTRAIL at four positions. In this study, the gene encoding mmTRAIL was cloned and recombinantly expressed in Escherichia coli at a yield of approximately 20-30 mg/L, which was two times higher than that of hTRAIL. SDS-PAGE showed that denatured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Lung cancer is one of the most common malignancies that seriously threatens human life [ 19 ]. Currently, drugs used in cancer treatment are not only toxic to cancer cells, but also toxic to normal cells [ 20 ]. However, natural products exist which have low toxicity and may represent good candidates for inhibiting tumor cell growth [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignancies that seriously threatens human life [ 19 ]. Currently, drugs used in cancer treatment are not only toxic to cancer cells, but also toxic to normal cells [ 20 ]. However, natural products exist which have low toxicity and may represent good candidates for inhibiting tumor cell growth [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding SPG C3Fab RR was designed according to its amino acid sequence 35 and optimized for recombinant expression in E. coli . The TRAIL gene was cloned in our previous study 36 . A flexible linker (G4S) 3 was inserted between IgBD and TRAIL.…”
Section: Methodsmentioning
confidence: 99%
“…To produce ABD-TRAIL, the ABD domain was genetically fused at the N-terminus of TRAIL as previously described 34 . The preparation of TRAIL has been described in a previous study 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, mmTRAIL and hTRAIL showed similar cytotoxicity in sensitive tumor cells, whereas mmTRAIL induced apoptosis in many resistant tumor cells more strongly than hTRAIL. 19 These results suggest that mmTRAIL might be a novel candidate for anticancer drugs.…”
Section: ■ Introductionmentioning
confidence: 91%
“…18 In our previous work, we found that mmTRAIL derived from rhesus monkey Macaca mulatta differed from hTRAIL at only four positions. 19 However, mmTRAIL was more soluble and stable than hTRAIL, resulting in yields of recombinant mmTRAIL that were 2-times higher than those of hTRAIL. Moreover, mmTRAIL and hTRAIL showed similar cytotoxicity in sensitive tumor cells, whereas mmTRAIL induced apoptosis in many resistant tumor cells more strongly than hTRAIL.…”
Section: ■ Introductionmentioning
confidence: 99%